2021
DOI: 10.1186/s12876-021-01669-w
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal ferritin levels predict development of poor outcomes in cirrhotic outpatients: a cohort study

Abstract: Background Both iron overload and iron deficient anemia can associate with cirrhosis. At the same time, inflammation might be continuously present in cirrhotic patients due to bacterial translocation and patients’ susceptibility to infections. Ferritin is a sensitive and widely available marker of iron homeostasis, in addition it acts as an acute phase protein. Therefore, we evaluated the prognostic potential of serum ferritin in the long-term follow-up of cirrhotic outpatients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Ferritin has previously been shown to be a predictor of poor outcomes 11,12 in patients with COVID-19. One meta-analysis of 25 studies and 5350 patients found that a higher serum ferritin level was independently associated with ARDS, mortality, and severe COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…Ferritin has previously been shown to be a predictor of poor outcomes 11,12 in patients with COVID-19. One meta-analysis of 25 studies and 5350 patients found that a higher serum ferritin level was independently associated with ARDS, mortality, and severe COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of Oikonomou were like those mentioned above -high serum ferritin levels are associated with poorer outcomes in patients with established decompensated cirrhosis [17]. Tornai et al found an association between high ferritin levels and mortality in Kaplan-Meier and univariate Cox regression analyses; however, they did not find high ferritin levels to be an independent predictor of mortality in the multivariate regression [18]. Most importantly, until now, no researcher has conducted a relevant meta-analysis.…”
Section: Introductionmentioning
confidence: 69%
“…It demonstrated, to some extent, that the serum ferritin cut-off values influence the study results and heterogeneity. Unfortunately, except for the study by Tornai 2021 [18] which described that high ferritin levels(>310 μg/l) were determined based on the 75th percentile of patients’ serum levels, the remaining studies, particularly those with the serum ferritin cut-off value of 200 ng/ml, did not provide a basis for indicating the source of the serum ferritin cut-off value. This makes it difficult to interpret the study results and heterogeneity according to the serum ferritin cut-off value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study followed 244 cirrhotic patients for 2 years, reported by Tornai et al , which found that high ferritin levels were associated with an increased risk of infection in patients with acquired decompensated cirrhosis (hazard ratio 2.335, 95%, CI 1.193–4.568, p = 0.013) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%